Erbium ytterbium doped waveguide amplifier / Nor Lailatul Hana Mohd Redzwan - Mohd Redzwan, Nor Lailatul Hana (2007)
In this project, the Erbium Ytterbium-doped waveguide amplifier was designed on a piece of the compact disc (CD). The CD is an optical component that has a refractive index value of 1.55. Fabricating the amplifier involves the process of CD preparation, coating with SU-8 polymer, soft bake, expose with UV, hard bake, cladding removal, splicing, fiber design onto the CD piece and make the PMMA layer onto the fiber. The fiber arrangement also involves in the project. The use of CD, polymer SU-8, and polymerPMMA are for fiber arrangement. The coating of the polymer layer was characterized by using a prism coupler and optical spectrum analyzer. The thickness and refractive index of-8 film on the CD was measured by using a prism coupler. The values with smaller standard deviation were considered as appropriate results to choose for their refractive index and thickness. The Gain (G) and Noise Figure (NF) of the amplifier were measured by using an optical spectrum analyzer. The power pump and corresponding pump current of the laser diode were recorded in the table. The Gain and Noise Figure were measured at several different pump powers. At 5, 10, 20, 30, 40, 50, 60, 70, 80, 90 and 100 mW of the pump power, the Gain of amplifier were -18.14, -2.71, 15.73, 21.80, 24.41, 25.94,26.92, 27.67, 28.27, 28.70 and 29.13 dB respectively. At these pump powers, the NoiseFigure of amplifier were 18.34, 5.79, 2.29, 2.08, 2.09, 2.07, 2.08, 2.05, 2.04, 2.07 and2.04 dB respectively. Lastly, the Gain was measured at fixed pump power at different signal wavelengths of light. At 1530.336, 1535.618, 1540.978, 1545.266, 1549.584,1555.040 and 1559.462 nm of signal wavelength, the amplifier Gain were 33.02, 28.14,25.58, 26.05, 26.05, 22.33 and 24.88 dB respectively. All the measurements were recorded in the appropriate tables. The relevant graphs were plotted based on the records in the tables.